How is silent ‘non-alcoholic fatty liver disease’ epidemic perceived in India? A community based cross sectional study - Lavekar, Anurag; Satyanarayana, Pradeep Tarikere; Lavekar, Anagha (International Journal Of Community Medicine And Public Health, 2019)
Background: One of the diseases assuming fast importance is non-alcoholic fatty liver disease (NAFLD) which is a clinical syndrome characterized by predominant macrovesicular steatosis of the liver which is an umbrella term for a range of liver conditions affecting people who drink little or no alcohol. Only mild to moderate elevation of serum transaminases which could be only laboratory abnormality found in NAFLD. So with this background, the study was started with the objectives of assessing the perceptions of general population regarding NAFLD and factors influencing perceptions of general population regarding NAFLD. Methods: It was a community based cross sectional study carried out for a period of 12 months from January 2018 to December 2018 among in Nanded, Maharashtra. Around 422 households were involved after simple random sampling. To assess perceptions a pretested semi-structured questionnaire was used which had 27 questions. All data collected was entered in Microsoft excel and analysed using SPSS v22. Results: Out of 422 participants, 147 (34.8%) were in the age group of 31-40 years, 333 (78.9%) were male participants, 179 (42.5%) were graduates, 284 (67.3%) belonged to joint family, 140 (33.2%) belonged to Modified BG Prasad classification 2018. 181 (42.9%) had satisfactory perception regarding NAFLD. Females, participants aged more than 40 years, nuclear family participants had better scores. Conclusions: The present study showed majority of the participants had little awareness of NAFLD regardless of their age, gender, or educational status. Awareness of NAFLD must be promoted for prevention, early detection, and treatment especially counseling by primary care physicians preponderant influence in preventive strategy for NAFLD breaking the chain of disease progression.